Pengaruh Upah, Masa Kerja dan Keterampilan terhadap Produktivitas Karyawan pada CV. Wuri Wijaya di Kabupaten Boyolali - Sri Lestari (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study: 1). To find out and analyze the effect of wages on employee productivity, 2). To find out and analyze the effect of length of service on employee productivity, 3). To find out and analyze the effect of skills on employee productivity. The population in this study were all employees of the production department of CV. Wuri Wijaya in Boyolali district. This study was conducted by sampling, with a saturated sample technique, a sample of 45 data was obtained. The analysis technique used multiple linear regression, the least squares method. The results of this study can be concluded that: 1). Wages have a positive but insignificant effect on employee productivity, 2). Length of service has a positive but insignificant effect on employee productivity, 3). Skills have a positive and significant effect on employee productivity.